2005
DOI: 10.1017/s0965539505001452
|View full text |Cite
|
Sign up to set email alerts
|

Management of Children With Cleft Lip and Palate: A Review Describing the Application of Multidisciplinary Team Working in This Condition Based Upon the Experiences of a Regional Cleft Lip and Palate Centre in the United Kingdom

Abstract: The management of children with cleft lip and palate presents many challenges but also many rewards. Our involvement with these children and their families often begins before birth and can extend into late adulthood. Affected individuals present a multiplicity of problems and effective management involves a wide range of specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 48 publications
1
57
0
11
Order By: Relevance
“…It also helps when informing about timing and type of surgery. To plan for the future, parents need to discuss the management and likely the treatment pathway at their own pace and at their own time, so that they are able to absorb the information [88]. Delayed repair of cleft can lead to impaired family and societal relationships with potential long-term psychological effects on the child.…”
Section: Psychological Managementmentioning
confidence: 99%
“…It also helps when informing about timing and type of surgery. To plan for the future, parents need to discuss the management and likely the treatment pathway at their own pace and at their own time, so that they are able to absorb the information [88]. Delayed repair of cleft can lead to impaired family and societal relationships with potential long-term psychological effects on the child.…”
Section: Psychological Managementmentioning
confidence: 99%
“…34 Sin embargo, la prevalencia exacta de labio y/o paladar hendido se desconoce debido a que muchos niños con la anomalía no nacen vivos y la mayoría de los estudios hacen el reporte de los niños nacidos vivos con LPH sindrómico o no. 35 El labio y paladar hendido en su variedad no sindrómi-ca representa el 70% de estas alteraciones, se presenta como un defecto aislado mientras que el sindrómico representa el 30% y está asociado a otras anormalidades estructurales. 2,13,11 La prevalencia de las hendiduras orales ha sido relacionada con el número de gestaciones de la madre, siendo más prevalente en los casos donde la madre es multípara.…”
Section: Epidemiologíaunclassified
“…This correlates with the report that 21%-37% of children with CL/P are reported to have other non-associated medical problems. 1 Parents of 26% (n = 29) of children with additional medical problems reported finding it difficult or impossible to access NHS dental care and 20% (n = 22) had suffered an episode of dental emergency including pain and infection. The difficulty in accessing primary dental care is likely to have long term implications on their oral health and in turn general health.…”
Section: Discussionmentioning
confidence: 99%
“…1 Children with CL/P may have complex dental problems and a number will require multidisciplinary care during their childhood and adolescence. 1 Associated dental defects can include: incisor displacement, presence of supernumerary teeth, hypodontia, enamel hypoplasia, microdontia and unusual shaped teeth, transposition and geminated/fused teeth. 2 Evidence has shown that this group of patients are at a higher risk of developing dental caries compared with the general population 3 ( Fig.…”
Section: Introductionmentioning
confidence: 99%